The First World War : analysis and interpretation. - Biagini, Antonello (Cambridge Scholars Publishing, 2015)
This volume is the result of an international conference held at Sapienza University of Rome in June 2014, which brought together scholars from different countries to re-analyse and re-interpret the events of the First World War, one hundred years after a young Bosnian Serb student from the "Mlada Bosna," Gavrilo Princip, "lit the fuse" and ignited the conflict which was to forever change the world. The Great War - initially on a European and then on a world scale - demonstrated the fragility of the international system of the European balance of powers, and determined the dissolution of the g.